Amidoethylation of anthracene hydride by n-aroylaziridines: inner-sphere single electron transfer (SET) and radical coupling confirmed - Lin, Pen-Yuan; Stamm, Helmut (Journal of chemical research online. Synopses, 1998)
Regioselectivity (near 1:1) of substitutive ring opening of 1-benzoyl-2-methylaziridine by anthracene hydride is incompatible with common nucleophilic attack and thus confirms the radical coupling path.